Impact of increased water vapor on precipitation efficiency over northern Eurasia. Issue 8 (25th April 2014) - Ye, Hengchun; Fetzer, Eric J.; Wong, Sun; Behrangi, Ali; Olsen, Edward T.; Cohen, Judah; Lambrigtsen, Bjorn H.; Chen, Luke
Abstract This study investigates the relationships among water vapor, precipitation efficiency, precipitation amount, and air temperature anomalies on monthly time scales over northern Eurasia for winter and summer 2003–2010. Daily precipitation and temperature records at 505 historical stations, and atmospheric total precipitable water vapor and relative humidity data from Atmospheric Infrared Sounders, are used for analysis. Results show that higher atmospheric precipitable water associated with warmer temperature directly contributes to winter precipitation amount but has little impact on winter precipitation efficiency. However, accelerated decreasing relative humidity associated with higher temperature is the primary factor in the reduction of precipitation efficiency and precipitation amount regardless of higher precipitable water in summer. This study suggests that there are evident seasonal differences in precipitation trend associated with air temperature changes over the study region. Air temperature modifies a key atmospheric water variable that directly controls precipitation for that particular season.